High mobility group box protein 1 sensitizes mononuclear cells to further contact with lipopolysaccharide - Jakub Piotrowski; Tomasz Jędrzejewski (Central European Journal of Immunology)
Fever is an adaptive host-defense response to infection and nowadays is rightly considered to be an expression of a healthy body and a well-functioning immune system. The condition is that it must be tightly regulated. Therefore, in individual cases, fever may be detrimental and should be treated. Specific excessive febrile reaction to pathogens which occurs after aseptic injuries is one among such cases. We previously found that among necrotic products, high mobility group box protein 1 (HMGB1) released from the site of aseptic injury affects immune effectors (cells) to mediate higher fever in response to further contact with bacterial lipopolysaccharide (LPS). Here we observed that intraperitoneal (i.p.) pre-injection of recombinant HMGB1 (5 µg/rat i.p.) provoked an increase in plasma levels of prostaglandin E2 (PGE2) in rats and augmented release of interleukin (IL)-1β and IL-6 after LPS administration at a dose of 50 µg/kg i.p. compared to rats pre-injected with saline or heat-denatured HMGB1. Furthermore, peripheral blood mononuclear cells (PBMCs) isolated from rats injected with HMGB1 were more sensitized to produce enhanced levels of IL-1β and PGE2 when stimulated with LPS in vitro (1 µg/ml/10 6 cells for 4 h) compared to control animals injected with saline or heat-denatured HMGB1. We also noted a significant increase in activation of nuclear factor κB (NF-κB) in cells isolated from rats injected with HMGB1. Altogether, the obtained results suggest that HMGB1 participates in priming of immune cells to further contact with pathogens.